Politična znanost pred novimi izzivi - Lukšič, Andrej (Teorija in praksa, 2022)
In the article, the author discusses the intrusion of environmental issues into the public and political spheres and how state authorities in the liberal-democratic system are dealing with it; due to its specific construction, which is constitutionally protected, such intrusion cannot directly intervene in material production, which is otherwise recognised as the main source of environmental damage. Political science, insofar as it is committed to the thought tradition established by Hobbes’ Leviethan and Machiavelli’s Ruler and acknowledged today as mainstream in political science, has a built-in conceptual blind spot as it focuses only on the ruler–political power relationship and cannot deal with the issue of the environment other than as a peripheral political problem. The author therefore defends the thesis that political science must be reconceptualised and the relationship between public power and material production must be brought to the fore if political science is to remain able to meet the demands of the historical moment and contribute to the thinking underlying the necessary transformation
Keywords: kapitalistični produkcijski način; Okoljska politika; Onesnaževanje; Politične vede